Weighted localization in mobile wireless networks. Issue 1 (24th November 2017) - Mahjri, Imen; Medjiah, Samir; Dhraief, Amine; Drira, Khalil; Belghith, Abdelfettah
Abstract : Localization of wireless devices is a crucial requirement for many emerging applications such as environmental monitoring, intelligent transportation, home automation, health‐care monitoring, and social networking. In this letter, we propose AWL a new aggregate weighted localization algorithm for mobile wireless networks. The proposed algorithm is distributed and requires low computational and communication overheads enabling its use in resource‐limited devices.